2012
DOI: 10.1007/s00384-012-1549-9
|View full text |Cite
|
Sign up to set email alerts
|

miRNA expressions in rectal cancer as predictors of response to neoadjuvant chemoradiation therapy

Abstract: Using microarray analysis of pretreatment FFPE rectal cancer tissues, we identified for the first time a group of miRNA predictors of response to neoadjuvant CRT. This, indeed, can lead to a significant improvement in patient selection criteria and personalized rectal cancer management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 52 publications
0
54
0
Order By: Relevance
“…38 fresh rectal biopsy samples [113] Neoadjuvant chemotherapy (oxaliplatin and 5-FU) and radiotherapy 14 miRNAs were differentially expressed in TRG1 patients compared to TRG > 1 (Mandard); 13 were confirmed by qRT-PCR Upregulated -miR-1183, miR-483-5p, miR-622, miR-125a-3p, miR-1224-5p, miR-188-5p, miR-1471, miR-671-5p, miR-1909, miR-630, miR-765 Down-regulated -miR-1274b, miR720 miR-622 and miR-630 had 100% sensitivity and 100% specificity 12 formalin-fixed paraffin embedded biopsy samples [114] Unknown 3 miRNA transcripts miR-16, miR-590-5p and miR-153 predicted complete versus incomplete response (Dworak). 2 transcripts miR-519c-3p and miR-561 predicted good versus poor response with a median accuracy of 100% 20 fresh rectal biopsy samples [115] Neoadjuvant chemotherapy (capecitabine or infusional 5-FU) and radiotherapy miR-215, miR190b and miR-29b-2 were overexpressed in non-responders while let-7e, miR-196b, miR-450a, miR-450b-5-p and miR-99a were overexpressed in responders (Mandard) 85 formalin-fixed paraffin embedded post-treatment samples [116] Neoadjuvant chemotherapy (capecitabine) and radiotherapy miR-21, miR-99, miR-125b, miR-125b1, let-7c and miR-490 upregulation correlated with TRG 1-2 (Mandard).…”
Section: Resultsmentioning
confidence: 99%
“…38 fresh rectal biopsy samples [113] Neoadjuvant chemotherapy (oxaliplatin and 5-FU) and radiotherapy 14 miRNAs were differentially expressed in TRG1 patients compared to TRG > 1 (Mandard); 13 were confirmed by qRT-PCR Upregulated -miR-1183, miR-483-5p, miR-622, miR-125a-3p, miR-1224-5p, miR-188-5p, miR-1471, miR-671-5p, miR-1909, miR-630, miR-765 Down-regulated -miR-1274b, miR720 miR-622 and miR-630 had 100% sensitivity and 100% specificity 12 formalin-fixed paraffin embedded biopsy samples [114] Unknown 3 miRNA transcripts miR-16, miR-590-5p and miR-153 predicted complete versus incomplete response (Dworak). 2 transcripts miR-519c-3p and miR-561 predicted good versus poor response with a median accuracy of 100% 20 fresh rectal biopsy samples [115] Neoadjuvant chemotherapy (capecitabine or infusional 5-FU) and radiotherapy miR-215, miR190b and miR-29b-2 were overexpressed in non-responders while let-7e, miR-196b, miR-450a, miR-450b-5-p and miR-99a were overexpressed in responders (Mandard) 85 formalin-fixed paraffin embedded post-treatment samples [116] Neoadjuvant chemotherapy (capecitabine) and radiotherapy miR-21, miR-99, miR-125b, miR-125b1, let-7c and miR-490 upregulation correlated with TRG 1-2 (Mandard).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the use of xenograft models has shown that miR-21 overexpression dramatically reduces the therapeutic efficacy of 5-FU [18]. Several studies have reported microRNAs such as miR-16, miR-590-5p, miR-153, miR-519c-3p, and miR-561, which are associated with CRT response, but these works did not include miR-21 [28,29]. However, changes in microRNA expression profiles were found in 35 patients with rectal carcinoma comparing pretherapeutic tissue with biopsies taken 2 weeks after treatment.…”
Section: Discussionmentioning
confidence: 96%
“…It is unclear whether each cancer type owns its specific cut-off value of individual miRNA, or shares the same cut-off value with others. (iii) Although several researches had reported the potential roles of miRNAs in chemo/radiation therapy [67], [68], [69], the efficiency and feasibility of miRNA therapies, such as interfering the expression of a specific miRNA or a set of them, and evaluating the side effect, still need to be investigated. (iv) Most of the included researches detected miRNA expression in cancer tissue samples, and that certainly matched the current clinical idea of golden standard for deterministic diagnosis.…”
Section: Discussionmentioning
confidence: 99%